Chinese New Year Celebrations: A Reproduction of Muslim Chinese Culture in Palembang - Nugroho; Idi , Abdullah; Mardiah , Anisatul; Zain , Zaki Faddad Syarif (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This article explores the unique phenomenon of cultural reproduction in Chinese Muslim communities through Chinese New Year celebrations. Traditionally a Chinese cultural festival is rich in heritage and ritual; these celebrations have been adapted with Islamic values, resulting in cultural acculturation and adaptation. Using a qualitative research approach grounded in anthropological-historical methods, the study involves in-depth interviews with key community members and participatory observations during celebrations. This approach provides a comprehensive understanding of how the fusion of Islamic principles and Chinese traditions creates a unique and dynamic narrative. The findings reveal that Chinese New Year celebrations in Chinese Muslim communities serve as a platform for maintaining cultural roots while fostering religious diversity. Ritual practices, such as communal prayers and the incorporation of halal principles into traditional Chinese feasts, highlight this blending of cultures. The celebrations also help redefine Muslim Chinese identity in a pluralistic society, positioning the event as a medium for countering cultural alienation and reinforcing a sense of belonging. This research contributes to the academic discourse on cultural reproduction by demonstrating how traditions can evolve to harmonize religious and cultural values. It also offers a methodological contribution by showcasing the effectiveness of combining anthropological-historical analysis with qualitative fieldwork in studying cultural adaptations. The insights gained from this study hold relevance for understanding the sustainability of Chinese Muslim culture and provide broader implications for fostering intercultural harmony in increasingly diverse societies.